KERJASAMA INDONESIA-KOREA SELATAN DALAM PENGEMBANGAN DESA MELALUI SISTEM SAEMAUL UNDONG (Studi Kasus Kerjasama Lintas Batas Daerah Istimewa Yogyakara-Gyeongsangbuk-Do) - Firstyarinda Valentina Indraswari (Department of International Relations, Brawijaya University, 2015)
Abstract The role of sub-state is getting wider and strategic in achieving the national interest of the state. The scholars sees this entity could works beyond it’s state in implementing their foreign policy. This capability could bring a positive and a negative impact within the state and toward international system. The specific role of this sub-state, such as province, districs, and village or rural area, has been studied in various sector including in the concept of sister city and cross border cooperation. The studies also covers various issues that needs multiactor participation to resolve it. The issues are such as environment, rural development, healthy, conflict rehabilitation, etc.This research tend to analyze the cooperation between Special Region of Yogyakarta and Gyeongsangbuk-Do in the scope of rural development issue. These provinces already cooperate for 10 years under various programmes cover by Saemaul Undong system. This is the Korean system in developing rural area and has been adopted in 14 states until today. By using cross border cooperation concept, this qualitative research found that these provinces has reached the third phase of cooperation process. The last phase, the fourth one, still face a difficult path because of the limitation authority of the local government. Various factors such as economic, culture, historical experience also booster the cooperation. Keywords: Cross Border Cooperation, Saemaul Undong, Special Region of Yogyakarta, Gyeongsangbuk-Do